Application of social psychology in supply chain management: A review - Prashant Singh; Ravi Kumar Jain; Ranjana Sharma (International Journal of Management, Economics and Social Sciences (IJMESS), 2021)
Behavioral operations management (BOM) is a rapidly growing field. It relaxes the assumption that "human being is rational" in the decision-making process, considers behavioral and cognitive aspects rooted in psychology to develop models for operations, and processes in production and manufacturing industries. Supply chain management (SCM), being a sub-domain of operations management (OM), has been investigated by combining various social psychology variables and supply chain elements. This article provides a literature review of similar studies. The article focuses on social psychology factors namely: trust, power, attribution theory, social network analysis, compliance, and social preference. This review found that it is imperative for firms to make their supply chains more effective especially when they are operating within competitive business environments. Since a supply chain network consists of various levels with one or more individuals at each level, the interaction between them is mandatory for the efficient functioning of the supply chain. Human behavior is a crucial characteristic to be considered while understanding the supply chain as it can influence the supply chain network's performance and decisions.
Keywords: D2; D23; 330; Behavioral supply chain management; social psychology; human behavior; social network analysis; social preference